1999
DOI: 10.1007/s003600050196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and photoperiod on thermogenesis in plateau pikas ( Ochotona curzoniae ) and root voles ( Microtus oeconomus )

Abstract: We examined the effects of temperature and photoperiod on metabolic thermogenesis and the thermogenic characteristics of brown adipose tissue in plateau pikas (Ochotona curzoniae) and root voles (Microtus oeconomus), the dominant species of small mammals in the alpine meadow ecosystems on the Qinghai-Tibetan Plateau. Pikas and voles were acclimated in the following groups: (1) Long day-warm temperature (16L:8D, 23 degrees C) (2) Long day-cold temperature (16L:8D, 5 degrees C), (3) short day-warm temperature (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 27 publications
7
31
1
Order By: Relevance
“…Both obligatory and adaptive thermogenesis (RMR and NST) are commonly employed in response to acute cold stress in small mammals living in temperate area (Heldmaier, 1971;Heldmaier and Buchberger, 1985;Hammond and Wunder, 1995;Wang et al, 1999;Li et al, 2001;Hammond and Kristan, 2000;Zhang and Wang, 2006;Zhang and Wang, 2007). In the present study RMR, NST max and NST generally increased with consecutively lower ambient temperatures, whereas the difference in NST max and NST were not statistically different between 8 and -15°C.…”
Section: Thermoregulation and Thermogenesissupporting
confidence: 39%
“…Both obligatory and adaptive thermogenesis (RMR and NST) are commonly employed in response to acute cold stress in small mammals living in temperate area (Heldmaier, 1971;Heldmaier and Buchberger, 1985;Hammond and Wunder, 1995;Wang et al, 1999;Li et al, 2001;Hammond and Kristan, 2000;Zhang and Wang, 2006;Zhang and Wang, 2007). In the present study RMR, NST max and NST generally increased with consecutively lower ambient temperatures, whereas the difference in NST max and NST were not statistically different between 8 and -15°C.…”
Section: Thermoregulation and Thermogenesissupporting
confidence: 39%
“…Through UCP1-mediated proton leakage from the mitochondrial respiratory chain, energy that is derived from metabolic fuels is dissipated as heat (Nicholls and Locke 1984;Krauss et al 2005), which, in turn, is essential for eVective thermoregulation in small mammals (Argyropoulus and Harper 2002). It has been found that many small mammals showed enhanced NST (Rafael et al 1985a;Merritt and Zegers 1991;JeWmow et al 2004) associated with increased BAT mass, mitochondrial protein (MP) concentrations, cytochrome c oxidase (COX) activity, and UCP1 mRNA level and protein expression in winter conditions (Rafael et al 1985b;Wang et al 1999;Li et al 2001;Li and Wang 2005).…”
Section: Introductionmentioning
confidence: 97%
“…LCT is often season and acclimatization dependent (McDevitt and Speakman 1994, Marchand 1996). Exposure to cold increases the metabolic rate in non-hibernating small mammals (Wang et al 1999, Cichon et al 2002 and it decreases immunocompetence (Cichon et al 2002). We hypothesized that compared to cool but stable temperature (6 C), fluctuating cool temperatures (1 C -12 C) could be even more challenging for small animals, due to the constant adjustment in thermoregulation it requires.…”
mentioning
confidence: 99%